Analisis Implementasi Pendekatan Tarl terhadap Hasil Belajar IPAS Kelas VI di SDN Sendangmulyo 02 - Pramudya Dwi Ratna Sari; Husni Wakhyudin; Darsimah Darsimah (Journal on Education, 2025)
This study analyzes the implementation of the Teaching at the Right Level (TaRL) approach on the learning outcomes of sixth-grade students at SDN Sendangmulyo 02 in the subject of Social Science (IPAS). According to Law No. 20 of 2003, the curriculum is designed to create effective learning experiences with flexibility tailored to students' needs. This research employs a mixed-methods approach, incorporating both quantitative and qualitative methods, with a pretest-posttest experimental design. Observations revealed differences in student abilities, categorized into three groups: needing guidance, proficient, and highly proficient. Through the application of TaRL, students are expected to achieve a better understanding aligned with their individual capabilities. Posttest results indicate a significant improvement in learning outcomes, with the average score rising from 60 to 80, and 85% of students meeting the Minimum Competency Criteria (KKTP). These findings demonstrate that the TaRL approach, emphasizing problem-based learning, is effective in enhancing students' understanding and learning outcomes, as well as increasing student engagement in the learning process. This study recommends the use of similar approaches for developing more relevant and adaptive learning at the elementary school level.